2023
DOI: 10.3390/su15054479
|View full text |Cite
|
Sign up to set email alerts
|

Towards Adaptive Governance of Urban Nature-Based Solutions in Europe and Latin America—A Qualitative Exploratory Study

Abstract: The concept and application of nature-based solutions (NBS) have been rapidly progressing in Europe and Latin America, reflecting a transition in the way that urban governance is perceived. There is a large call for the collaborative, polycentric, and interdisciplinary governance of NBS. However, research on options for operationalising these governance processes in different contexts is still insufficient. This study explores and analyses the operationalisation of NBS adaptive governance in Europe and Latin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…There seems to be broad agreement on the need for locally adaptive NBS, tailored to specific contexts and challenges, including the wide range of governance arrangements, political regimes, socio-economic factors, as well as cultural and historical considerations prevalent across both the GN and the GS (Davies and Lafortezza 2017 ; Kauark-Fontes et al 2023 ). However, it is notable that countries in the GN often possess more substantial financial resources for NBS due to their higher income levels and well-established environmental policies (Kauark-Fontes et al 2023 ). Conversely, this financial advantage is not typically enjoyed by countries in the GS, leading them to encounter challenges in securing funding for large-scale NBS projects (Castelo et al 2023 ; Kauark-Fontes et al 2023 ).…”
Section: The Debate On Nbs and The Urban Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…There seems to be broad agreement on the need for locally adaptive NBS, tailored to specific contexts and challenges, including the wide range of governance arrangements, political regimes, socio-economic factors, as well as cultural and historical considerations prevalent across both the GN and the GS (Davies and Lafortezza 2017 ; Kauark-Fontes et al 2023 ). However, it is notable that countries in the GN often possess more substantial financial resources for NBS due to their higher income levels and well-established environmental policies (Kauark-Fontes et al 2023 ). Conversely, this financial advantage is not typically enjoyed by countries in the GS, leading them to encounter challenges in securing funding for large-scale NBS projects (Castelo et al 2023 ; Kauark-Fontes et al 2023 ).…”
Section: The Debate On Nbs and The Urban Contextmentioning
confidence: 99%
“…However, it is notable that countries in the GN often possess more substantial financial resources for NBS due to their higher income levels and well-established environmental policies (Kauark-Fontes et al 2023 ). Conversely, this financial advantage is not typically enjoyed by countries in the GS, leading them to encounter challenges in securing funding for large-scale NBS projects (Castelo et al 2023 ; Kauark-Fontes et al 2023 ). Furthermore, policy support for NBS in the GS tends to exhibit greater variability, or being completely absent, resulting in difficulties when trying to coordinate efforts across diverse government agencies (Breen et al 2020 ).…”
Section: The Debate On Nbs and The Urban Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, nature-based solutions (NbS) were seen as an important adaptation option for climate change and canal management. NbS were defined as actions to conserve, sustainably use, and restore natural or altered ecosystems, which can effectively and adaptively respond to the challenges facing our society today, while enriching human well-being and biodiversity [34,35].…”
Section: Existing Practices Based On Nature-based Solutions (Nbs)mentioning
confidence: 99%
“…This could better overcome sectoral and discipline isolation (silos), lack of promotion of shared knowledge, segregation of resources, and limited instruments and tools for different forms of collaboration in policy and planning. To this extent, polycentric and more flexible governance models that can be context sensitive, allow for a confluence of actors, deeper citizen relationships, learning and knowledge sharing, and power sharing such as adaptive governance (Egusquiza et al 2019, Albert et al 2021, Martin et al 2021, Kauark-Fontes et al 2023 or mosaic governance (Gulsrud et al 2018, Buijs et al 2019, Pauleit et al 2019) are suggested by the literature. Lastly, policies should enable the participation of all stakeholders from the very beginning of NBS development within the policies themselves and at the very start of NBS programs and projects, with equal voices and needs.…”
Section: The Way Forward: Insights Gained For Nbs Integration In Urba...mentioning
confidence: 99%